WATER QUALITY ASSESSMENT OF RIVER GOMATI AT JAUNPUR (U.P.) INDIA - PRAMOD KUMAR SINGH; ARVIND KUMAR SINGH (International Journal of Pharma and Bio Sciences, 2014)
This study was aimed to estimate the physico-chemical characteristics and their variation across the stretch of river Gomati flowing through the city of Jaunpur. These parameters were measured at five sampling sites, namely Kalichabad Ghat (Control site), Gular Ghat (Site I), Hanuman Ghat (Site II), Baluwa Ghat (Site III) and Miyanpur Ghat (Site IV). The water samples were collected and analyzed for a period of one year during June 2010 and May 2011. For the study certain parameters such as pH, temperature, DO, BOD and COD were taken. It was found that at all the sites, generally higher pH values were recorded in the summer month and least during the rainy season. Temperature was minimum at the control site (30.2 0C) and maximum at site IV (33.8 0C). The DO showed a decreasing trend from the control site to site IV. The BOD value ranged from 2.7 mg/L in the month of December at the control site to 16.4 mg/L in the month of June at site IV. The COD values also showed an increasing trend from the control site to site IV.